The improvable self: enacting model citizenship and sociality in research on 'new recovery'. (2nd November 2019) - Fomiatti, Renae; Moore, David; Fraser, Suzanne
Abstract: 'New recovery' has become an increasingly prominent feature of alcohol and other drug policy and treatment responses. Research has been an important site in the emergence of new recovery but its assumptions, politics and productive role in constituting the realities of new recovery have received little critical scrutiny. In this article, we draw on John Law's typology of 'simplification practices' to analyse the reality-making practices operating in two recent and influential developments in research on new recovery: the Assessment of Recovery Capital (ARC) scale and the Social Identity Model of Recovery (SIMOR). Despite their purported novelty, the ARC scale and the SIMOR enact a familiar divide between the individual subject and the social environment. The sociality and material conditions of people who use drugs are constituted as manageable problems that can and should be carefully monitored, controlled and ultimately changed in order to recover. This particular enactment of the 'social' underpins and reinforces a hierarchical logic in which individual subjects are obliged to recover by controlling and changing their social environments through enterprise and activity. Despite their good intentions, both the ARC scale and the SIMOR erase the political, economic, legal and cultural relations that shape the lives of people who uses drugs. We consider new recovery's claims to 'newness' and question what kinds of transformations are made possible, as well as foreclosed, by its focus on the improvable self. We conclude by suggesting an alternative focus that prioritises the resources and relations conducive to 'living well'.